Polyvinyl alcohol film, method for producing polyvinyl alcohol film, and polarizing film

By controlling the tension range of polyvinyl alcohol-based films stretched in water at different temperatures, the problems of insufficient film dyeability and stretchability were solved, enabling the manufacture of polarizing films with high polarization and no polarization unevenness, thus improving productivity.

CN119286173APending Publication Date: 2025-01-10MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411483819.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2015-06-24
Filing Date
2016-06-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing technology, polyvinyl alcohol films have insufficient dyeability and stretchability, resulting in low polarization degree and uneven polarization during the manufacturing process of polarizing films. This makes it difficult to achieve thinner dimensions in terms of width and length, and also results in low productivity.

Method used

By controlling the tension range of polyvinyl alcohol films stretched in water at different temperatures, specifically ensuring that the tension along the film flow direction in water at 30℃ and 50℃ satisfies a specific formula relationship, it is ensured that the film maintains high polarization and no polarization unevenness during the thinning process.

Benefits of technology

The high dyeability and stretchability of polyvinyl alcohol-based films have been achieved, enabling the manufacture of polarizing films with high polarization and no polarization unevenness, thus improving productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098205810000171
    Figure BDA0005098205810000171
  • Figure BDA0005098205810000181
    Figure BDA0005098205810000181
Patent Text Reader

Abstract

The invention relates to a polyvinyl alcohol-based film, a method for producing the polyvinyl alcohol-based film, and a polarizing film. Provided is a polyvinyl alcohol-based film which has excellent dyeability and stretchability, and which is characterized by being capable of providing a polarizing film that has high degree of polarization and does not have unevenness in polarization even when the thickness of the film is increased and reduced. When the thickness is D (mm), the tension when stretched 6 times the flow direction (MD direction) of the film in water at 30 DEG C is A (N / mm2), and the tension when stretched 6 times the flow direction (MD direction) of the film in water at 50 DEG C is B (N / mm2), expressions (1) and (2) are satisfied. Formula (1) 0.6 < = D * A < = 1.2 Formula (2) 0.2 < = D * B < = 0.4.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on June 23, 2016, with application number 201680029754.7 and invention name “Polyvinyl alcohol-based film, method for producing polyvinyl alcohol-based film and polarizing film”. Technical Field

[0002] The present invention relates to a polyvinyl alcohol film, and more particularly to a polyvinyl alcohol film having excellent dyeability and stretchability as a raw roll of a polarizing film and used for producing a polarizing film having excellent polarization performance with high productivity, a production method thereof, and a polarizing film obtained by using the polyvinyl alcohol film. Background Art

[0003] Polarizing film is made by dyeing the original roll of polyvinyl alcohol film with iodine or other pigments and then stretching it. For example, the polyvinyl alcohol film is swollen with warm water, then dyed with iodine, stretched to align the iodine molecules, cross-linked with boric acid or other cross-linking agents to maintain the stretched state, washed and dried. Sometimes the above-mentioned water swelling, dyeing, stretching, and boric acid cross-linking processes are also replaced in order, or multiple processes are carried out simultaneously. The common point is that the polyvinyl alcohol film is continuously rolled out from the roll, and a winder or roller is used to apply appropriate tension along the flow direction, while conveying in the horizontal direction.

[0004] The polarizing film is used as a key component of liquid crystal display devices such as mobile information terminals and televisions. In recent years, with the high brightness and high precision of liquid crystal displays, polarizing films with high light transmittance and high polarization degree are desired. Furthermore, with the large screen and thinner type of liquid crystal televisions, polarizing films with further width, length and thinness than existing products are desired.

[0005] In order to meet the above expectations, a polyvinyl alcohol film with excellent dyeability and stretchability and thin width and length is required. When the dyeability of the polyvinyl alcohol film is low, sufficient polarization cannot be obtained, and there is a tendency to easily produce uneven polarization. When the stretchability of the polyvinyl alcohol film is low, fracture occurs in the manufacturing process of the polarizing film, and therefore, a thin polarizing film with a long width and length cannot be manufactured. Of course, the continuous manufacturing interruption due to fracture greatly reduces the productivity of the polarizing film. Furthermore, when the stretchability is low, the pigment cannot be fully oriented, and therefore, there is a tendency to reduce polarization or easily produce uneven polarization. The thinner the polyvinyl alcohol film becomes, the more difficult it is to improve the dyeability and stretchability. In addition, in the coating type polarizing plate for the purpose of so-called thinning, the above-mentioned dyeing, stretching and other processes are also necessary. Although they are present on the supporting film, it is expected that the dyeability and stretchability of the polyvinyl alcohol film after coating will be improved.

[0006] In order to improve the dyeability of polyvinyl alcohol-based films, a method of controlling the bath temperature in the swelling process has been proposed (see, for example, Patent Documents 1 and 2). In addition, a polarizing plate using a polyvinyl alcohol-based film having a stretchability within a specific range has been proposed (see, for example, Patent Document 3).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-065309

[0010] Patent Document 2: Japanese Patent Application Publication No. 2014-197050

[0011] Patent Document 3: Japanese Patent Application Publication No. 2002-236212 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] However, the techniques disclosed in Patent Documents 1 and 2 have the following problem: even if the swelling degree can be controlled by the bath temperature, if the tension applied to the polyvinyl alcohol film in the bath is inappropriate, a uniform swelling state cannot be obtained, and the pigment is not uniformly adsorbed in the subsequent dyeing process.

[0014] In addition, the technology disclosed in the above-mentioned Patent Document 3 limits the stress (tension) when the polyvinyl alcohol film is stretched to 4 to 6 times in water, but in the actual manufacture of polarizing films, since the water temperature of each process is different, it is not sufficient to obtain a tension suitable for all processes. It should be noted that the water temperature is mostly carried out at a relatively low temperature of 30°C in the swelling and dyeing processes, and is mostly carried out at a relatively high temperature of 50°C in the stretching and boric acid crosslinking processes.

[0015] Therefore, in this invention, under such background, a polyvinyl alcohol film having excellent dyeability and stretchability and capable of obtaining a polarizing film having high polarization degree and no polarization unevenness even when the width and length are reduced and the film is thinned is provided.

[0016] Solutions for solving problems

[0017] Therefore, in view of the above situation, the inventors of the present invention have repeatedly conducted in-depth research and found that: for a polyvinyl alcohol film obtained by discharging an aqueous solution of a polyvinyl alcohol resin and casting it onto a casting mold to form a film, and continuously drying it, when it is stretched in water at different temperatures, the tension in each water is made to be within a specific range, especially focusing on the tension in water at a high temperature of 50°C, so that the polyvinyl alcohol film produced can be manufactured into a polarizing film with high polarization degree and no polarization unevenness while being thinned in width and length.

[0018] That is, the gist of the present invention is a polyvinyl alcohol-based film, characterized in that the thickness is D (mm), the tension when the film is stretched to 6 times in the flow direction (MD direction) of the film in water at 30° C. is A (N / mm 2 The tension when the film is stretched to 6 times in the flow direction (MD direction) of the film in 50°C water is set as B (N / mm 2 ), the following equations (1) and (2) are satisfied.

[0019] Formula (1) 0.6 ≤ D × A ≤ 1.2

[0020] Formula (2) 0.2 ≤ D × B ≤ 0.4

[0021] In addition, the present invention also provides: a method for producing the polyvinyl alcohol-based film; and a polarizing film obtained by using the polyvinyl alcohol-based film.

[0022] Effects of the Invention

[0023] The polyvinyl alcohol-based film of the present invention has excellent dyeability and stretchability, and can provide a polarizing film having a high degree of polarization and no polarization unevenness even when the width and length are reduced and thinned, and can also be produced with high productivity. DETAILED DESCRIPTION

[0024] Hereinafter, the present invention will be described in detail.

[0025] The polyvinyl alcohol film of the present invention must be a polyvinyl alcohol film having a thickness of D (mm) and a tension of A (N / mm) when the film is stretched to 6 times in the flow direction (MD direction) of the film in water at 30°C. 2 The tension when the film is stretched to 6 times in the flow direction (MD direction) of the film in 50°C water is set as B (N / mm 2 ), the following equations (1) and (2) are satisfied:

[0026] Formula (1) 0.6 ≤ D × A ≤ 1.2

[0027] Formula (2) 0.2 ≤ D × B ≤ 0.4

[0028] Preferably, the polyvinyl alcohol film satisfies the following formulae (1') and (2'):

[0029] Formula (1') 0.65 ≤ D × A ≤ 1.15

[0030] Formula (2') 0.25 ≤ D × B ≤ 0.39

[0031] In particular, a polyvinyl alcohol-based film satisfying the following formulas (1") and (2") is preferred.

[0032] Formula (1") 0.7 ≤ D × A ≤ 1.1

[0033] Formula (2") 0.27 ≤ D × B ≤ 0.38

[0034] Regarding the above formulas (1) to (1"), if the value of D×A is too low, the film may be deformed in the swelling step and the dyeing step, which is not preferred. Even if it is too high, sufficient dyeing in the dyeing step becomes difficult, which is not preferred.

[0035] In the above formulas (2) to (2"), when the value of D×B is too low, the polarization degree when forming a polarizing film decreases, which is not preferred, and when it is too high, the polarizing film is easily broken when it is manufactured, which is not preferred.

[0036] Regarding the above formulas (1) to (1") and the above formulas (2) to (2"), the value of the thickness D of the polyvinyl alcohol film is preferably less than 0.04 mm in terms of thinning the polarizing film, and is particularly preferably less than 0.03 mm in terms of further thinning the polarizing film, and is further preferably 0.01 to 0.03 mm in terms of avoiding breakage of the polarizing film.

[0037] Furthermore, the polyvinyl alcohol-based film of the present invention preferably satisfies the following formula (3), particularly preferably satisfies the following formula (3'), and further preferably satisfies the following formula (3").

[0038] Formula (3) 0.2≤B / A≤0.5

[0039] Formula (3') 0.25 ≤ B / A ≤ 0.4

[0040] Formula (3") 0.3 ≤ B / A ≤ 0.35

[0041] Regarding the above formulas (3) to (3"), when the value of B / A is too low, the polarization degree when forming a polarizing film tends to decrease, and when it is too high, the polarizing film tends to be easily broken when it is produced.

[0042] In addition, for the polyvinyl alcohol film of the present invention, the tension A when stretched 6 times in the flow direction (MD direction) of the film in water at 30°C is preferably 15 to 40 N / mm 2 , particularly preferably 18 to 35 N / mm 2, more preferably 20 to 30 N / mm 2 .

[0043] When the value of the tension A is too low, the film tends to be easily deformed in the swelling step and the dyeing step, and when it is too high, sufficient dyeing tends to be difficult in the dyeing step.

[0044] Furthermore, for the polyvinyl alcohol film of the present invention, the value of the tension B when stretched to 6 times in the flow direction (MD direction) of the film in water at 50°C is preferably 3 to 15 N / mm 2 , particularly preferably 4 to 12 N / mm 2 , more preferably 5 to 10 N / mm 2 .

[0045] When the value of the tension B is too low, the degree of polarization when forming a polarizing film tends to decrease, and when it is too high, the polarizing film tends to be easily broken when it is produced.

[0046] In the polyvinyl alcohol film of the present invention, when the storage modulus in water at 30° C. is E1 (Pa) and the storage modulus in water at 50° C. is E2 (Pa), the value of E2 / E1 is preferably 0.25 to 0.30, particularly preferably 0.26 to 0.29.

[0047] When the value of E2 / E1 is too low, the polarization degree of the obtained polarizing film tends to decrease, and when it is too high, the polarizing film tends to be broken during production.

[0048] Furthermore, in the polyvinyl alcohol-based film of the present invention, the storage elastic modulus E1 in water at 30° C. is preferably 9 to 12 MPa in terms of transportability.

[0049] In terms of transportability, the storage modulus E2 in water at 50° C. is preferably 2 to 4 MPa.

[0050] Hereinafter, the method for producing a polyvinyl alcohol film of the present invention, that is, a method for producing a polyvinyl alcohol film by discharging an aqueous solution of a polyvinyl alcohol resin, casting it on a casting mold to form a film, and continuously drying it, will be described.

[0051] As the polyvinyl alcohol-based resin used in the present invention, an unmodified polyvinyl alcohol-based resin is generally used, that is, a resin produced by saponifying polyvinyl acetate obtained by polymerizing vinyl acetate. If necessary, a resin obtained by saponifying a copolymer of vinyl acetate and a small amount (usually less than 10 mol %, preferably less than 5 mol %) of a component that can copolymerize with vinyl acetate can also be used. As components that can copolymerize with vinyl acetate, for example, unsaturated carboxylic acids (for example, including salts, esters, amides, nitriles, etc.), olefins with 2 to 30 carbon atoms (for example, ethylene, propylene, n-butene, isobutylene, etc.), vinyl ethers, unsaturated sulfonates, etc. can be cited. In addition, a modified polyvinyl alcohol-based resin obtained by chemically modifying the hydroxyl group after saponification can also be used.

[0052] In addition, as the polyvinyl alcohol-based resin, a polyvinyl alcohol-based resin having a 1,2-diol structure in the side chain can also be used. The polyvinyl alcohol-based resin having a 1,2-diol structure in the side chain can be produced, for example, by the following methods: (i) a method of saponifying a copolymer of vinyl acetate and 3,4-diacetoxy-1-butene; (ii) a method of saponifying and decarbonating a copolymer of vinyl acetate and vinyl ethylene carbonate; (iii) a method of saponifying and deketalizing a copolymer of vinyl acetate and 2,2-dialkyl-4-vinyl-1,3-dioxolane; (iv) a method of saponifying a copolymer of vinyl acetate and glycerol monoallyl ether; etc.

[0053] The weight average molecular weight of the polyvinyl alcohol resin is preferably 100,000 to 300,000, particularly preferably 110,000 to 280,000, and further preferably 120,000 to 260,000. If the weight average molecular weight is too small, it is difficult to obtain sufficient optical properties when the polyvinyl alcohol resin is formed into an optical film, and if it is too large, it is difficult to stretch the polyvinyl alcohol film during the manufacture of the polarizing film. It should be noted that the weight average molecular weight of the polyvinyl alcohol resin is a weight average molecular weight measured by the GPC-MALS method.

[0054] The average saponification degree of the polyvinyl alcohol resin used in the present invention is usually preferably 98 mol% or more, particularly preferably 99 mol% or more, further preferably 99.5 mol% or more, and particularly preferably 99.8 mol% or more. If the average saponification degree is too low, there is a tendency that sufficient optical properties cannot be obtained when the polyvinyl alcohol film is formed into a polarizing film.

[0055] Here, the average saponification degree in the present invention is measured in accordance with JIS K 6726.

[0056] As the polyvinyl alcohol-based resin used in the present invention, two or more types of resins having different modified substances, modification amounts, weight average molecular weights, average saponification degrees, etc. may be used in combination.

[0057] The polyvinyl alcohol film of the present invention can be continuously produced by preparing a polyvinyl alcohol resin aqueous solution (film-forming stock solution) using the above-mentioned polyvinyl alcohol resin, discharging the aqueous solution and casting it on a casting mold, forming a film by casting, and drying. For example, it can be produced by the following steps.

[0058] Step (A) is a step of preparing an aqueous solution of a polyvinyl alcohol-based resin.

[0059] Step (B) is a step of casting a polyvinyl alcohol-based resin aqueous solution on a casting mold to form a film.

[0060] Step (C) is a step of heating and drying the formed film by bringing it into contact with a plurality of metal heating rolls.

[0061] Step (D) is a step of heat-treating the obtained film using hot air.

[0062] Here, examples of the casting mold include a casting drum (drum-shaped roller) and an endless belt. A casting drum is preferred from the viewpoints of wide width, long length, and excellent uniformity of film thickness.

[0063] Hereinafter, the case where the casting mold is a casting drum will be described as an example.

[0064] First, the above-mentioned step (A) will be described.

[0065] In step (A), it is preferred that the polyvinyl alcohol resin is first washed with water and then dehydrated using a centrifuge or the like to form a polyvinyl alcohol resin wet cake having a water content of 50 wt % or less. If the water content is too high, it tends to be difficult to form an aqueous solution of a desired concentration.

[0066] The polyvinyl alcohol-based resin wet cake is dissolved in warm water or hot water to prepare a polyvinyl alcohol-based resin aqueous solution.

[0067] The method for preparing the aqueous solution of the polyvinyl alcohol resin is not particularly limited. For example, it can be prepared using a heated multi-screw extruder. Alternatively, the aforementioned polyvinyl alcohol resin wet cake can be placed in a dissolution tank equipped with upper and lower circulating flow-generating stirring blades, and water vapor can be blown into the tank to dissolve and prepare an aqueous solution of the desired concentration.

[0068] In the present invention, the latter is preferred from the viewpoint of improving the degree of polarization, and preparation by pressure dissolution at 120° C. or higher is more preferred.

[0069] The polyvinyl alcohol-based resin aqueous solution preferably contains, in addition to the polyvinyl alcohol-based resin, a plasticizer and at least one surfactant selected from the group consisting of nonionic, anionic and cationic surfactants as required from the viewpoint of film-forming properties.

[0070] Examples of the plasticizer used in the present invention include glycerin, diglycerin, triglycerin, ethylene glycol, triethylene glycol, polyethylene glycol, trimethylolpropane, etc. Among them, glycerin is preferred because it is inexpensive.

[0071] When glycerin is used, the amount thereof is preferably 5 to 12% by weight, particularly preferably 6 to 11.5% by weight, and further preferably 7 to 11% by weight, based on the weight of the polyvinyl alcohol-based resin.

[0072] When the amount of the above-mentioned compounding is too small, the tension of the polyvinyl alcohol-based film in water tends to be increased, and when it is too large, the tension of the polyvinyl alcohol-based film in water tends to be insufficient.

[0073] As the surfactant used in the present invention, an anionic surfactant is preferred from the viewpoint of compatibility with the polyvinyl alcohol-based resin aqueous solution.

[0074] The resin concentration of the polyvinyl alcohol-based resin aqueous solution thus obtained is preferably 15 to 60% by weight, particularly preferably 17 to 55% by weight, and further preferably 20 to 50% by weight. When the resin concentration is too low, the drying load becomes large, thereby tending to reduce the productivity, and when it is too high, the viscosity becomes too high and uniform dissolution tends to be difficult.

[0075] In this way, a polyvinyl alcohol-based resin aqueous solution as a film-forming stock solution can be obtained. Next, the above-mentioned step (B) will be described.

[0076] The polyvinyl alcohol-based resin aqueous solution is subjected to a degassing treatment. Examples of the degassing method include static degassing and degassing using a multi-screw extruder equipped with a vent. As the multi-screw extruder equipped with a vent, a twin-screw extruder equipped with a vent is generally used.

[0077] After the degassing treatment, a certain amount of the polyvinyl alcohol-based resin aqueous solution was sequentially introduced into a T-slit die, discharged and cast onto a rotating casting drum to form a film by a casting method.

[0078] The resin temperature at the T-slit die outlet is preferably 80 to 100° C., particularly preferably 85 to 99° C. If the resin temperature is too low, the fluidity tends to be poor, and if it is too high, the resin tends to foam.

[0079] The viscosity of the polyvinyl alcohol-based resin aqueous solution when discharged is preferably 50 to 200 Pa·s, particularly preferably 70 to 150 Pa·s.

[0080] When the viscosity of the aqueous solution is too low, the fluidity tends to be poor, and when it is too high, casting tends to be difficult.

[0081] The discharge speed of the polyvinyl alcohol-based resin aqueous solution discharged from the T-slit die to the casting drum is preferably 0.2 to 5 m / min, particularly preferably 0.4 to 4 m / min, and further preferably 0.6 to 3 m / min.

[0082] When the discharge speed is too slow, productivity tends to decrease, and when it is too fast, casting tends to become difficult.

[0083] During the casting process, it is preferably carried out with a casting drum from the aspects of width, length, uniformity of film thickness, etc. As a casting drum, a metal plating for preventing scratches is usually used on the surface of stainless steel (SUS) with iron as the main component. As metal plating, for example, chrome plating, nickel plating, zinc plating, etc. can be cited, which can be used alone or in a stacked form of more than 2 layers. Among them, from the aspect of the durability of the drum surface, the outermost surface is preferably chrome-plated.

[0084] Hereinafter, the film forming method will be described by taking the case of using a casting drum as an example.

[0085] The width of the casting drum is preferably 4 m or more, particularly preferably 5 m or more. If the width of the casting drum is too small, it tends to be difficult to obtain a wide film.

[0086] The diameter of the casting drum is preferably 2 to 5 m, particularly preferably 2.4 to 4.5 m, and further preferably 2.8 to 4 m.

[0087] If the diameter is too small, the drying length tends to be insufficient and the speed tends to be difficult to generate, while if it is too large, the transportability tends to be reduced.

[0088] The rotation speed of the casting drum is preferably 3 to 50 m / min, particularly preferably 4 to 40 m / min, and further preferably 5 to 35 m / min. If the rotation speed is too slow, productivity tends to decrease, and if it is too fast, drying tends to be insufficient.

[0089] The surface temperature of the casting drum is preferably 40 to 99° C., particularly preferably 60 to 95° C. If the surface temperature is too low, drying tends to be poor, and if it is too high, foaming tends to occur.

[0090] The film was formed in this manner.

[0091] Next, the step (C) is described. The step (C) is a step of heating and drying the formed thin film by bringing it into contact with a plurality of metal heating rollers.

[0092] The polyvinyl alcohol film formed by the casting drum is dried by contacting the front and back of the film with a plurality of metal heating rollers alternately. The surface temperature of the metal heating roller is not particularly limited, but is usually preferably 60 to 150° C., more preferably 70 to 140° C. If the surface temperature is too low, the film tends to be poorly dried, and if it is too high, the film tends to be over-dried, resulting in poor appearance such as warping.

[0093] In the present invention, from the viewpoint of controlling the underwater tension of the polyvinyl alcohol-based film, the temperatures of the plurality of metal heating rollers are preferably in the order of the following conditions (a) to (d).

[0094] Condition (a)≥80℃

[0095] Condition (b) <80℃

[0096] Condition (c) ≥ 100℃

[0097] Condition (d)<100℃

[0098] It should be noted that the number of metal heating rollers is usually 10 to 30, and is appropriately set so as to satisfy the above-mentioned temperature conditions.

[0099] After drying with a metal heating roll, the obtained film is heat-treated with hot air in step (D). Next, the step (D) is described.

[0100] The heat treatment temperature is preferably 110 to 140° C., particularly preferably 115 to 135° C., and further preferably 120 to 130° C. If the heat treatment temperature is too low, the underwater tension of the polyvinyl alcohol film tends to be insufficient, while if it is too high, the underwater tension of the polyvinyl alcohol film tends to increase.

[0101] As the heat treatment method, a method using a floating dryer is preferred from the viewpoint of excellent temperature control.

[0102] The heat-treated film is cut at both ends and wound around a roll to obtain a roll-shaped polyvinyl alcohol-based film.

[0103] In terms of increasing the width of the polarizing film, the width of the polyvinyl alcohol film is preferably 4 m or more, particularly preferably 4.5 m or more, and further preferably 4.5 to 6 m in terms of avoiding breakage.

[0104] The length of the polyvinyl alcohol film is preferably 4 km or longer from the perspective of increasing the area of ​​the polarizing film, particularly preferably 4.5 km or longer from the perspective of further increasing the area, and further preferably 4.5 to 50 km from the perspective of transportation weight.

[0105] The polyvinyl alcohol film is preferably stretched 4 times in the film flow direction (MD direction) in an atmosphere of 20°C and 65%RH to a tension of 40 to 80 N / mm in terms of windability. 2 From the perspective of stability during storage, 43 to 75 N / mm is particularly preferred. 2 From the perspective of ease of controlling the underwater tension, 46 to 70 N / mm is more preferred. 2 .

[0106] The polyvinyl alcohol-based film has an in-plane retardation of preferably 50 nm or less, particularly preferably 40 nm or less, and further preferably 30 nm or less, from the viewpoint of uniformity of tension in water.

[0107] In this manner, the polyvinyl alcohol-based film of the present invention can be obtained.

[0108] The polyvinyl alcohol-based film of the present invention has excellent optical properties and can be suitably used as a polyvinyl alcohol-based film for optical use, and is particularly preferably used as a raw roll for a polarizing film.

[0109] Hereinafter, a method for producing a polarizing film using the polyvinyl alcohol-based film of the present invention will be described.

[0110] The polarizing film of the present invention is produced by rolling the polyvinyl alcohol film from a roll and conveying it in a horizontal direction, and then undergoing the steps of swelling, dyeing, boric acid cross-linking, stretching, washing, and drying.

[0111] The swelling process is implemented before the dyeing process. The swelling process can clean the dirt on the surface of the polyvinyl alcohol film, and by swelling the polyvinyl alcohol film, it also has the effect of preventing uneven dyeing. In the swelling process, water is usually used as the treatment liquid. The main component of the treatment liquid only needs to be water, and a small amount of iodinated compounds, surfactants and other additives, alcohol, etc. can also be added. The temperature of the swelling bath is usually about 10 to 45°C, and the immersion time in the swelling bath is usually about 0.1 to 10 minutes. In addition, stretching operation can also be performed during the treatment as needed.

[0112] The dyeing process is carried out by contacting the film with a liquid containing iodine or a dichroic dye. An aqueous solution of iodine-potassium iodide is usually used, and it is appropriate that the concentration of iodine is 0.1 to 2 g / L and the concentration of potassium iodide is 1 to 100 g / L. The dyeing time is practically about 30 to 500 seconds. The temperature of the treatment bath is preferably 5 to 50° C. In addition to the aqueous solvent, the aqueous solution may also contain a small amount of an organic solvent that is compatible with water. In addition, a stretching operation may also be performed during the treatment as required.

[0113] The boric acid crosslinking process is carried out using a boron compound such as boric acid or borax. The boron compound is used in the form of an aqueous solution or a water-organic solvent mixture at a concentration of about 10 to 100 g / L. From the perspective of stabilizing polarization performance, potassium iodide is preferably coexisted in the liquid. The temperature during the treatment is preferably about 30 to 70°C, the treatment time is preferably about 0.1 to 20 minutes, and a stretching operation can be performed during the treatment as needed.

[0114] The stretching process is preferably stretched 3 to 10 times, preferably 3.5 to 6 times, in a uniaxial direction. At this time, a small amount of stretching (to prevent shrinkage in the width direction, or stretching above it) may also be performed in a direction perpendicular to the stretching direction. The temperature during stretching is preferably 30 to 170°C. Furthermore, as long as the stretching ratio is finally set to the aforementioned range, the stretching operation can be performed only in one stage and can be implemented at any stage in the manufacturing process.

[0115] The cleaning process is carried out, for example, by immersing the polyvinyl alcohol film in an aqueous iodide solution such as water or potassium iodide, so that the precipitate produced on the surface of the film can be removed. When using an aqueous potassium iodide solution, the concentration of potassium iodide can be about 1 to 80 g / L. The temperature during the cleaning treatment is usually 5 to 50° C., preferably 10 to 45° C. The treatment time is usually 1 to 300 seconds, preferably 10 to 240 seconds. It should be noted that water cleaning and cleaning using an aqueous potassium iodide solution can also be appropriately combined.

[0116] The drying step may be performed in the air at 40 to 80° C. for 1 to 10 minutes.

[0117] The polarization degree of the polarizing film is preferably 99.5% or more, more preferably 99.8% or more. If the polarization degree is too low, the contrast in the liquid crystal display tends to be unable to be ensured.

[0118] The degree of polarization is generally calculated as follows: the transmittance (H) measured at a wavelength λ in a state where two polarizing films are overlapped so that their orientation directions are in the same direction. 11 ), and the light transmittance (H1) measured at a wavelength λ in a state where two polarizing films are overlapped so that the orientation directions are orthogonal to each other, are calculated according to the following formula.

[0119] 〔(H 11 -H1) / (H 11 +H1)〕 1 / 2

[0120] Furthermore, the single-unit transmittance of the polarizing film of the present invention is preferably 42% or more. If the single-unit transmittance is too low, it tends to be impossible to achieve high brightness of a liquid crystal display.

[0121] The single-piece transmittance is a value obtained by measuring the light transmittance of a single polarizing film using a spectrophotometer.

[0122] In this manner, the polarizing film of the present invention can be obtained, and the polarizing film of the present invention is suitable for producing a polarizing plate with less color unevenness.

[0123] Hereinafter, the method for producing the polarizing plate of the present invention will be described.

[0124] The polarizing film of the present invention is bonded to one or both sides of the polarizing film with an optically isotropic resin film as a protective film with the aid of an adhesive to form a polarizing plate. Examples of the protective film include films or sheets of cellulose triacetate, cellulose diacetate, polycarbonate, polymethyl methacrylate, cycloolefin polymer, cycloolefin copolymer, polystyrene, polyether sulfone, polyarylate, poly-4-methylpentene, polyphenylene ether, and the like.

[0125] The lamination is performed by a known method, for example, by uniformly applying a liquid adhesive composition to the polarizing film, the protective film, or both, laminating and pressing the two, and then heating or irradiating with active energy rays.

[0126] In order to reduce the thickness of the polarizing film, a curable resin such as a polyurethane resin, an acrylic resin, or a urea resin may be applied to one or both sides of the polarizing film and cured to form a polarizing plate instead of the protective film.

[0127] The polarizing film formed by the polyvinyl alcohol-based film obtained by the manufacturing method of the present invention also has excellent in-plane uniformity of polarization performance, and is preferably used in: mobile information terminals, personal computers, televisions, projectors, billboards, desktop computers, electronic clocks, word processors, electronic paper, game consoles, camcorders, cameras, photo frames, thermometers, audio, automobiles, liquid crystal display devices of mechanical instruments, sunglasses, anti-glare glasses, stereo glasses, wearable displays, anti-reflection layers for display elements (CRT, LCD, organic EL, electronic paper, etc.), optical communication equipment, medical equipment, building materials, toys, etc.

[0128] Example

[0129] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to the following Examples unless the gist of the invention is exceeded.

[0130] In addition, "part" and "%" in the examples are by weight.

[0131] <Measurement Conditions>

[0132] (1) Tensile tension in water (N / mm 2 )

[0133] A test piece of length (MD direction) 50 mm × width (TD direction) 35 mm × thickness D (mm) was cut out from the obtained polyvinyl alcohol film, and the two ends in the longitudinal direction were clamped with chucks of 35 mm width so that the chuck spacing was 20 mm. Then, the stress (N) when stretched to 6 times at a speed of 18 mm / min in the MD direction was measured using a spring balance in water at 30°C and 50°C. The value obtained by dividing the above stress by the cross-sectional area of ​​the film was taken as the tensile tension (N / mm 2 ).

[0134] (2) Tensile tension in the atmosphere (N / mm 2 )

[0135] After the obtained polyvinyl alcohol film was conditioned in an atmosphere of 20°C and 65% RH for one day, a test piece of length (MD direction) 120 mm × width (TD direction) 15 mm × thickness D (mm) was cut out, and the two ends in the length direction were clamped with chucks of 15 mm width in a manner that the chuck spacing was 50 mm using the "Precision Universal Testing Machine, AUTOGRAPH (AG-IS)" manufactured by Shimadzu Corporation. The stress (N) when stretched to 4 times at a speed of 1000 mm / min in the MD direction was measured in an atmosphere of 20°C and 65% RH. The value obtained by dividing the above stress by the cross-sectional area of ​​the film is taken as the tensile tension in the atmosphere (N / mm 2 ).

[0136] (3) In-plane phase difference (nm)

[0137] A test piece of 20 cm in length (MD direction) x 20 cm in width (TD direction) was cut out from the obtained polyvinyl alcohol film, and the in-plane retardation (nm) was measured using a two-dimensional birefringence evaluation system (manufactured by Photonic Lattice, Inc.: “PA-110L”).

[0138] (4) Polarization degree (%), single body transmittance (%)

[0139] A sample of 4 cm in length×4 cm in width was cut out from the obtained polarizing film, and the degree of polarization (%) and the single body transmittance (%) were measured using an automatic polarizing film measuring apparatus (VAP7070 manufactured by JASCO Corporation).

[0140] (5) Uneven polarization

[0141] A test piece of 30 cm in length and 30 cm in width was cut out from the obtained polarizing film and clamped between two polarizing plates in a crossed prism state (single-body transmittance 43.5%, polarization degree 99.9%) at an angle of 45°. The optical color unevenness was observed in transmission mode using a light box with a surface illumination of 14000 lux (lx) and evaluated according to the following criteria.

[0142] (Evaluation Criteria)

[0143] ○···No color unevenness

[0144] △···Slight color unevenness

[0145] ×···There is color unevenness

[0146] <Example 1>

[0147] (Manufacture of polyvinyl alcohol-based films)

[0148] In a 5000L dissolving tank were added 1000kg of a polyvinyl alcohol resin having a weight average molecular weight of 142000 and a saponification degree of 99.8 mol%, 2500kg of water, 105kg of glycerol as a plasticizer, and 0.25kg of sodium dodecyl sulfate as a surfactant. The mixture was heated to 150°C and pressure-dissolved while stirring to obtain a polyvinyl alcohol resin aqueous solution having a resin concentration of 25%.

[0149] Next, the polyvinyl alcohol resin aqueous solution is supplied to a twin-screw extruder equipped with an exhaust port. After degassing, the aqueous solution temperature is set to 95°C, discharged from a T-slit die outlet and cast onto a casting drum rotating at 20 m / min to form a film. The resulting film is peeled off from the casting drum and dried while the surface and back of the film are alternately contacted with a total of 20 metal heating rollers. The above-mentioned metal heating rollers are arranged in a temperature sequence of 90°C, 70°C, 110°C, and 85°C. Next, hot air at 140°C is blown from both sides of the film for heat treatment, and finally cut and wound to obtain a rolled polyvinyl alcohol film (film thickness 0.03 mm, width 5 m, length 5 km). The properties of the resulting polyvinyl alcohol film are shown in Table 1.

[0150] (Manufacturing of polarizing film)

[0151] The obtained polyvinyl alcohol film was rolled out from a roll, transported in the horizontal direction, immersed in a water tank at a water temperature of 30°C and swollen, and then stretched to 1.7 times in the MD direction. Next, it was immersed and dyed in a 30°C aqueous solution formed by 0.5g / L iodine and 30g / L potassium iodide, stretched to 1.6 times in the MD direction, and then immersed in an aqueous solution (50°C) composed of 40g / L boric acid and 30g / L potassium iodide for boric acid crosslinking, and uniaxially stretched to 2.1 times in the MD direction. Finally, it was washed with a potassium iodide aqueous solution, and then dried at 50°C for 2 minutes to obtain a polarizing film with a total stretch ratio of 5.7 times. No breakage was caused in the above-mentioned manufacture, and the properties of the obtained polarizing film are shown in Table 2.

[0152] <Example 2>

[0153] A polyvinyl alcohol-based film and a polarizing film were obtained in the same manner as in Example 1 except that the heat treatment was performed by blowing hot air at 130° C. The obtained polarizing film was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.

[0154] <Example 3>

[0155] In Example 1, except that the rotation speed of the casting drum was changed to 10 m / min, the film thickness was 0.06 mm, and the heat treatment was performed by blowing hot air at 120° C., a polyvinyl alcohol-based film and a polarizing film were obtained in the same manner as in Example 1. The obtained polarizing film was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.

[0156] <Example 4>

[0157] In Example 1, a polyvinyl alcohol-based film and a polarizing film were obtained in the same manner as in Example 1 except that the rotation speed of the casting drum was changed to 10 m / min, the film thickness was set to 0.06 mm, and the heat treatment temperature was set to 110° C. The obtained polarizing film was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.

[0158] <Comparative Example 1>

[0159] In Example 1, a polyvinyl alcohol-based film and a polarizing film were obtained in the same manner as in Example 1 except that the rotation speed of the casting drum was changed to 10 m / min, the film thickness was set to 0.06 mm, and the heat treatment temperature was set to 100° C. The obtained polarizing film was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.

[0160] <Comparative Example 2>

[0161] A polyvinyl alcohol film was obtained in the same manner as in Example 1 except that the heat treatment temperature was 150° C. The polyvinyl alcohol film was used to produce a polarizing film, but when producing a polarizing film of 1 km in length, breakage occurred during stretching in the boric acid crosslinking step, and the target polarizing film could not be obtained.

[0162] <Comparative Example 3>

[0163] In Example 1, a polyvinyl alcohol-based film and a polarizing film were obtained in the same manner as in Example 1 except that the temperature of all the metal heating rolls was set to 80° C. The obtained polarizing film was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.

[0164] [Table 1]

[0165]

[0166] [Table 2]

[0167]

[0168] For the polyvinyl alcohol films of Examples 1 to 4, the thickness was defined as D (mm), and the tension when the film was stretched to 6 times in the flow direction (MD direction) of the film in water at 30° C. was defined as A (N / mm 2 The tension when the film is stretched to 6 times in the flow direction (MD direction) of the film in 50°C water is set as B (N / mm 2 ), the values ​​of D×A and D×B both satisfy equations (1) and (2). In contrast, for the polyvinyl alcohol film of comparison example 1, the value of D×B is outside the range of equation (2). For the polyvinyl alcohol films of comparison examples 2 and 3, the value of D×A is outside the range of equation (1), and the value of D×B is also outside the range of equation (2).

[0169] It is also found that Examples 1 to 4 are superior to Comparative Examples 1 and 3 in terms of polarization properties of polarizing films obtained from the polyvinyl alcohol-based films. Furthermore, in Comparative Example 2, a polarizing film could not be obtained due to breakage.

[0170] Furthermore, the storage elastic moduli E1 and E2 of the polyvinyl alcohol films obtained in Examples 3 and 4 and Comparative Example 1 were measured according to the following method, and the value of E2 / E1 was calculated.

[0171] (6) Storage modulus (MPa)

[0172] A test piece of 25 mm in length (MD direction) x 5 mm in width (TD direction) was cut out from the obtained polyvinyl alcohol film, and the storage modulus in water at 30° C. and 50° C. was measured using DVA-225 manufactured by ITK CO., LTD. The detailed test conditions are as follows.

[0173] Frequency: 10Hz

[0174] Chuck spacing: 15mm

[0175] Load: Dynamic strain along MD direction is 0.3%, static-dynamic ratio (ratio of static strain to dynamic strain) is 6

[0176] E2 / E1 was calculated from the storage modulus E1 (MPa) after immersion in water at 30°C for 10 minutes and the storage modulus E2 (MPa) after immersion in water at 50°C for 10 minutes. The film thickness before immersion in water was used for calculating the storage modulus in water.

[0177] The measurement results were as follows: Example 3: E2 / E1=0.28, Example 4: E2 / E1=0.27, Comparative Example 1: E2 / E1=0.25, and it was confirmed that when the value of E2 / E1 was low, the degree of polarization when the polarizing film was formed was reduced.

[0178] The above embodiments show specific aspects of the present invention, but the above embodiments are merely examples and are not to be construed as limiting. Various modifications that are obvious to those skilled in the art are intended to be within the scope of the present invention.

[0179] Industrial Applicability

[0180] The polarizing film formed by the polyvinyl alcohol-based film obtained by the manufacturing method of the present invention also has excellent in-plane uniformity of polarization performance, and is preferably used in: mobile information terminals, personal computers, televisions, projectors, billboards, desktop computers, electronic clocks, word processors, electronic paper, game consoles, camcorders, cameras, photo frames, thermometers, audio, automobiles, liquid crystal display devices of mechanical instruments, sunglasses, anti-glare glasses, stereo glasses, wearable displays, anti-reflection layers for display elements (CRT, LCD, organic EL, electronic paper, etc.), optical communication equipment, medical equipment, building materials, toys, etc.

Claims

1. A polyvinyl alcohol film, characterized in that: Set the thickness to D (mm), The tension when the film is stretched to 6 times in the flow direction (MD direction) of the film in 30°C water is defined as A (N / mm 2 ), The tension when the film is stretched to 6 times in the flow direction (MD direction) of the film in 50°C water is defined as B (N / mm 2 )hour, Satisfying the following equations (1) and (2), Formula (1) 0.6 ≤ D × A ≤ 1.2 Formula (2) 0.2≤D×B≤0.

4.

2. The polyvinyl alcohol film according to claim 1, characterized in that: Satisfies the following formula (3): Formula (3) 0.2≤B / A≤0.

5.

3. The polyvinyl alcohol film according to claim 1 or 2, characterized in that: When the storage modulus in water at 30° C. is defined as E1 (Pa) and the storage modulus in water at 50° C. is defined as E2 (Pa), E2 / E1 is 0.25 to 0.

30.

4. The polyvinyl alcohol film according to claim 1 or 2, characterized in that: The thickness D of the polyvinyl alcohol-based film is 0.04 mm or less.

5. The polyvinyl alcohol film according to claim 1 or 2, characterized in that: The polyvinyl alcohol-based film has a width of 4 m or more and a length of 4 km or more.

6. The polyvinyl alcohol film according to claim 1 or 2, characterized in that: In an atmosphere of 20°C and 65% RH, the tension when the film is stretched to 4 times along the flow direction (MD direction) is 40 to 80 N / mm 2 .

7. The polyvinyl alcohol film according to claim 1 or 2, characterized in that: The in-plane phase difference is 50 nm or less.

8. A method for producing a polyvinyl alcohol-based film, characterized in that: The method for producing the polyvinyl alcohol film according to any one of claims 1 to 7 is characterized in that the polyvinyl alcohol film is produced through the following steps (A) to (D). Step (A), a step of preparing an aqueous solution of a polyvinyl alcohol-based resin; Step (B) is a step of casting a polyvinyl alcohol-based resin aqueous solution onto a casting mold to form a film; Step (C) is a step of heating and drying the formed film by bringing it into contact with a plurality of metal heating rollers; Step (D) is a step of heat-treating the obtained film using hot air.

9. The method for producing a polyvinyl alcohol-based film according to claim 8, characterized in that: In the step (A), 5 to 12% by weight of glycerin is blended with the polyvinyl alcohol-based resin.

10. The method for producing a polyvinyl alcohol-based film according to claim 8 or 9, characterized in that: The temperatures of the plurality of metal heating rollers in the step (C) are in the order of the following conditions (a) to (d), Condition (a)≥80℃ Condition (b) <80℃ Condition (c) ≥ 100℃ Condition (d)<100℃.

11. The method for producing a polyvinyl alcohol-based film according to claim 8 or 9, characterized in that: The heat treatment temperature in the step (D) is 110 to 140°C.

12. A polyvinyl alcohol-based film, characterized in that: The present invention is produced by the production method according to any one of claims 8 to 11.

13. A polarizing film, characterized in that: The polyvinyl alcohol film is formed of the polyvinyl alcohol film according to any one of claims 1 to 7 and 12.

Citation Information

Patent Citations

  • Polarizing plate and liquid crystal display device which uses the same

    JP2002236212A

  • Method for manufacturing polarizing film, polarizing film, polarizing plate, optical film and image display device

    JP2006065309A

  • Production method of polarizing film

    JP2014197050A